Pojęcie regionu ojczystego, regionow świata, "dużej" i "małej" ojczyzny na przykładzie Dolnego Śląska = The concepts of the home region, world regions, homeland and home country. The development of the historical, national and regional consciousness on the example of Lower Silesia - Burda, Bogumiła (Zielona Góra: Lubuskie Towarzystwo Naukowe)
We live in the times when identification with one`s nation, state or local region plays a particularly significant role since the transmission of cultural heritage conditions the preservation of culture. At present it can be observed that cultural heritage should be understood above all in the categories of history, that is the story of previous generations, living tradition, folklore, language, cultural benefits as well as achievements manifested both in terms of remains, monuments as well as oral history.
Keywords: Dolny Śląsk; mała ojczyzna; region; ojczyzna